Influence of the Iceland mantle plume on crustal accretion at the inflated Reykjanes Ridge: Magma lens and low hydrothermal activity? art. no. 2524 - Chen, YJ (Journal of Geophysical Research, 2003)
[1] A simple ridge model is applied to the hot spot-influenced, slow spreading Reykjanes Ridge in the North Atlantic to explore the effects of both mantle temperatures and hydrothermal cooling due to the Iceland mantle plume on the thermal structure and crustal accretion at this ridge. The objective of this study is not only to fit existing observations but also to raise important questions for future field programs to test. Does a magma chamber similar to that at the East Pacific Rise exist beneath the inflated Reykjanes Ridge north of the transition site at 59 degreesN and if it does, at what depths? Modeling results of this study show that with increased magma supply a long-lived magma chamber could be present at the lower crust if hydrothermal activity is comparable to elsewhere of the Mid-Atlantic Ridge. More importantly, modeling results predict a shallow magma chamber beneath the inflated Reykjanes Ridge north of 59 degreesN if it is associated with low hydrothermal activity. Since the recent observations of the extremely low incidence of high-temperature vents along the Reykjanes Ridge was interpreted as the indication for the diffusive flow being the dominant mode of hydrothermal circulation there, not as the evidence for low hydrothermal activity, the questions raised here call for more field observations at the inflated Reykjanes Ridge north of 59 degreesN against these testable model predictions and thus to resolve these important issues. Geochemistry & Geophysics SCI(E) 0 ARTICLE B11 null 108